Does "the" Dutch INGO exist? Mapping a decade of financial and organisational change. Issue 6 (17th August 2020) - Schulpen, Lau; van Kempen, Luuk
ABSTRACT: This article traces the development of Dutch INGOs over 2010–2017 using a unique dataset of 366 organisations. Overall, the Dutch INGO sector has remained quite financially stable and shows resilience in offsetting declines in one type of income by intensifying income generation from another source. However, this overall picture obscures diverging dynamics for subgroups based on the size of their budget. Analysis at the sector and size-class levels helps to understand the internal dynamics of the Dutch INGO world and provides a valuable reference point for unravelling its rich diversity.